2020
DOI: 10.1111/jch.13869
|View full text |Cite
|
Sign up to set email alerts
|

Lurking in plain sight: Hypertension awareness and treatment among New York City taxi/for‐hire vehicle drivers

Abstract: Uncontrolled hypertension may be worse for certain occupational groups, including taxi and for-hire vehicle (FHV) drivers. In 2015, one in three US adults had hypertension, 1 based on hypertensive values at systolic blood pressure (SBP) >140 mm Hg and/or diastolic blood pressure (DBP) 90 mm Hg. 2 Approximately, 50% (35 million) of those with hypertension had uncontrolled hypertension. 1 The 2017 American College of Cardiologists/American Heart Association guidelines lowered the hypertensive-range values such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Of these publications, 12 stratified length of residence into <10 years and >10 years [26,28,32,34,35,38,39,42,58,70,78,81]. The other studies included immigrants with <10 years of residence in the USA [30,65], <15 and >15 years [29,44,53,54,56], <20 and >20 years [41,50,66,74,80], or <25 and >25 years of residence [14]. Eleven studies [16,40,47,51,52,55,61,64,67,75,77] reported only average years of residence.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these publications, 12 stratified length of residence into <10 years and >10 years [26,28,32,34,35,38,39,42,58,70,78,81]. The other studies included immigrants with <10 years of residence in the USA [30,65], <15 and >15 years [29,44,53,54,56], <20 and >20 years [41,50,66,74,80], or <25 and >25 years of residence [14]. Eleven studies [16,40,47,51,52,55,61,64,67,75,77] reported only average years of residence.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Immigrant-Related Health-, Dietary-, and Lifestyle-Related Community-Related generational status [14] nativity [26,35,42,54,72] health behaviors [16,34] immigrant concentration [49,68] length of residence in USA [14,26,36,39,47,72,81] agricultural work [31,33,61] health assimilation; health literacy; nutrition transition; dietary characteristics [41,47,51,80] community factors [58,68] migration history [34] income; sociodemographic factors [31,32,47,53,68,70] healthcare services access and utilization [56,62] immigration [15,[27][28][29][30][31]45,82] ethnicity [37,44] food insecurity [64,65] acculturation …”
Section: Immigration-relatedmentioning
confidence: 99%
See 2 more Smart Citations
“…High rates among African immigrants are thought to be the result of high carbohydrate and high sodium diets brought from home countries to sedentary host country environments. In one study, 80% of African immigrants employed driving taxi and for-hire vehicles in New York had hypertensive-range blood pressure readings (Narang et al, 2020). Secondary analysis of data on African immigrants in the National Health Institute Survey suggests that sedentarism, food insecurity, and length of residence are all important predictors of HTN in this population (Ojih & Bradford, 2022).…”
Section: Subjective Social Status and Health Among Immigrant Populationsmentioning
confidence: 99%